(untitled) (PETITUM, 2022)
ABSTRACT: The main problem in this study is the Role of the Justice Collaborator Legal Review In Money Laundering Crime Disclosure. This study aims to determine the role of justice collaborator witnesses in their position as evidence in cases of money laundering crimes, also to know the role of witness and victim protection institutions against justice collaborator witnesses in criminal cases. Money laundering based on Law Number 13 of 2006 concerning the Protection of Witnesses and Victims. This research is a normative legal research, by using a statute approach, a case approach, and a conceptual approach. The results of the studies are (1) the role of the Justice Collaborator Witness in his position as evidence in the crime of money laundering is to reveal a criminal act or the occurrence of a criminal act that he was involved in, thereby maximizing the return of assets from the proceeds of a criminal act, providing information to law enforcement officers, providing testimony in the judicial process in order to uncover larger crimes. The role of justice collaborators in Indonesia is still found in crucial problems, which lie in legal instruments. ABSTRAK: Pokok permasalahan dalam penelitian ini adalah Tinjauan Hukum Justice Collaborator dalam Mengungkap Kasus Tindak Pidana Pencucian Uang. Pokok masalah dibagi menjadi dua sub masalah: 1. Bagaimanakah peranan saksi justice collaborator dalam kedudukannya sebagai alat bukti pada tindak pidana pencucian uang, 2. Bagaimanakah peranan lembaga perlindungan saksi dan korban terhadap saksi justice collaborator pada tindak pidana pencucian uang berdasarkan Undang-Undang Nomor 13 Tahun 2006 tentang Perlindungan Saksi dan Korban. Adapun sumber data penelitian ini adalah penelitian hukum normatif, dengan menggunakan pendekatan undang-undang (statute approach), pendekatan kasus (case approach), dan pendekatan konseptual (conceptual approach). Hasil penelitian menunjukkan bahwa (1) Peranan Saksi Justice Collaborator dalam kedudukannya sebagai alat bukti dalam tindak pidana pencucian uang adalah mengungkap suatu tindak pidana atau terjadinya suatu tindak pidana yang ia terlibat di dalamnya, sehingga memaksimalkan pengembalian asset dari hasil suatu tindak pidana, memberikan informasi kepada aparat penegak hukum, memberikan kesaksian di dalam proses peradilan guna membongkar kejahatan tindak pidana lebih besar. Peran justice collaborator di Indonesia masih ditemukan permasalahan krusial, yang terletak pada instrumen hukum.